2009
DOI: 10.1897/08-483.1
|View full text |Cite
|
Sign up to set email alerts
|

A microtiter‐plate‐based cytochrome P450 3A activity assay in fish cell lines

Abstract: Abstract-Enzymes belonging to the cytochrome P450 3A (CYP3A) subfamily play an important role in the metabolism of endogenous substances and xenobiotics, including pharmaceuticals. Xenobiotics can alter CYP3A expression and activity, and therefore, changes in CYP3A activity may serve as a biomarker of xenobiotic exposure. To determine changes in CYP3A enzyme activity for environmental risk assessment of xenobiotics including pharmaceuticals, high-throughput assays are needed, but these are missing for fish cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Nevertheless the good positive correlation between BFCOD, cyp1a gene transcription and dealkylating activities underlines the need for further investigation of genes encoding this activity and indicates BFCOD as a possible general marker of CYP induction by PAHs, in this species. A cyp3a induction model using primary mullet hepatocytes would be needed to establish whether cyp3a catalytic assays are reliable markers of PAHs contamination, as suggested in other species (Christen et al, 2009), and to investigate the relationship between cyp3a and BFCOD.…”
Section: Hismentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless the good positive correlation between BFCOD, cyp1a gene transcription and dealkylating activities underlines the need for further investigation of genes encoding this activity and indicates BFCOD as a possible general marker of CYP induction by PAHs, in this species. A cyp3a induction model using primary mullet hepatocytes would be needed to establish whether cyp3a catalytic assays are reliable markers of PAHs contamination, as suggested in other species (Christen et al, 2009), and to investigate the relationship between cyp3a and BFCOD.…”
Section: Hismentioning
confidence: 99%
“…Response of cyp1a towards PAHs has been extensively studied and is known to be regulated by the aryl hydrocarbon receptor (AhR) (Stegeman and Hahn, 1994;Hahn, 1998). On the other hand, while cyp3a is known to be involved in the metabolism of several drugs (Hasselberg et al, 2008;Christen et al, 2009), its role and regulation in fish is still matter of debate. Few studies have directly addressed its involvement in the response to environmental contaminants, and field data are lacking altogether.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, BFC is believed to be the specific substrate for CYP3A (Christen et al, 2009). Our study showed that BFCOD activity was inhibited by KTZ in a non-competitive manner in salmon (Figure 3).…”
Section: Inhibition Patternmentioning
confidence: 68%
“…Catalytic activities of CYP3A have been determined in different fish by use of different substrates [16,21,22]. It was found that CYP3A enzymatic activity in fish can easily be determined by application of a modified human CYP3A activity assay, in which the conversion of a substrate by CYP3A to a fluorescent product is determined [14,15,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%